(untitled) (Research, Society and Development, 2024)
Leprosy is a chronic infectious disease caused by the Mycobacterium leprae complex, primarily affecting the skin and peripheral nerves. It is transmitted through close and prolonged contact with an infected person. Leprosy is endemic in Brazil and is highly debilitating when diagnosed late and/or not treated adequately. Among the various organs affected, the kidneys can be involved through different pathophysiological mechanisms, with a particular focus on glomerulonephritis. This study aims to describe and discuss the case of a previously healthy patient who had a delayed diagnosis of multibacillary leprosy, leading to renal injury and subsequent chronicity of the condition. This is an observational, descriptive, qualitative study utilizing data obtained from the patient’s medical record and photographic records made during hospitalization. Through the examination of clinical manifestations, diagnosis, and treatment of the disease, the study aims to contribute to the understanding of the pathophysiology of renal disease in Mycobacterium leprae infection.